The Characteristic of Variable Frequency Drive for Water Flow Control in the SFC Plant - Sefi Novendra Patrialova; Destiarga Husein Wardhana; Lucky Putri Rahayu; Tedy Agasta (IPTEK The Journal of Engineering, 2021)
One of several techniques to control fluid flow-rate through a pump is using variable frequency drive.  This paper presents how experiment be able to perceive the characteristic of variable frequency drive (VFD) to control water flow-rate in the Simulator Flow Control (SFC) plant. The SFC plant is developed for a fluid course learning simulator. The user would be able to set the desired value of frequency or flow-rate through a convenient interface. To provide it, the characteristic of VFD-frequency-to-flow-rate must be firstly observed, as reported in this paper. The fluid flow-rate control is designed without an electric valve, but using VFD to drive the 250 Watt water pump. In this first development, the SFC Plant successfully work with various water flow-rate from 2 Liter per minute until 20 Liter per minute by changing the frequency input of VFD. The water flow-rate was measured by manual rotameter, the flow sensor has not been applied yet in this first development. In this experiment, the VFD’s frequency was set from 10 Hz to 36 Hz with 2 Hz intervals. Result showed that VFD frequency is proportional to water flow-rate. The higher frequency given to VFD, the faster rotational motor of water pump generated and then given rise to water flow-rate. Using linear graphic approach, the characteristic is shown through the linearity coefficient of 0,68 and constant value of 3.43. This characteristic value would be useful for open-loop-control and user interface programming in next step of development.